The Spectrum and Orbit of a Fireball Producing Mesospheric Irregularity and Implications for Meteor Mass Deposition - Guozhu Li; Zhi Wu; Yi Li; Lianhuan Hu; Wenjie Sun; Haiyong Xie; Xiukuan Zhao; Iain M. Reid; Baiqi Ning; Libo Liu (The Astrophysical Journal, 2023)
The physical properties of meteoroids producing meteor plasma non-field-aligned irregularities (NFAI) in the Earth’s atmosphere are poorly known. Here we report a complete picture of a fireball and mesospheric NFAI that it produced for the first time. Simultaneous radar and optical observations were made by the recently completed facility, Meteor and ionospheric Irregularity Observation System. The observations show that the mesospheric NFAI were clustered into three patches where the optical meteor flares took place, instead of being generated continuously along the whole meteor path. It is very likely that nanometer-or-larger-sized dust particles could be directly generated via meteoroid fragmentation at the flaring points and thus promote the generation of NFAI patches. The properties of the parent meteoroid show a chondrite type and a Jupiter family comet orbit, with Na/Mg and Fe/Mg intensity ratios of 1.5 and 1, respectively, photometric mass of about 4 g, and fragmentation strengths of around 10–74 kPa. The results suggest that the direct generation of dust particles, which was previously observed in the atmospheric disintegration of a kiloton-scale meteoroid, could be extended to the much smaller gram-scale meteoroids. Since meteoroids having such characteristics or more fragile material are not unusual, further studies leading to a better understanding of meteor mass deposition in the upper atmosphere, which consider the dust particles directly generated via gram-scale meteoroid fragmentation, are extremely important.